Cobertura vegetal, diversidade de plantas lenhosas e serviços ecossistêmicos de provisão em três núcleos susceptíveis à desertificação - Macêdo, Maria Soraya (2022)
Desertification poses many potential threats to native species persistence on drylands globally, possibly reducing biodiversity, biological and economic productivity of these areas. Among the main causes of desertification are the unsustainable crop expansion, overgrazing and the chronic and continuous use of native vegetation which has established a degradation rate greater than 30% of the total of these areas. Although its alarming scenario in which drylands are worldwide, there are only few studies highlining the consequences of this disturbance to the Brazilian semi-arid region. This study aimed to evaluate the current state of vegetation cover of three areas susceptible to desertification in the state of Ceará, in the Brazilian semiarid, and to assess the regeneration potential of the native vegetation, how preserved are the ecosystem services and the diversity of local plants. In order to answer these questions, we mapped and classified three polygons in areas susceptible to desertification according to the current state of woody vegetation cover, structure and configuration of landscape. We performed a phytosociological inventory of each woody species individual within these polygons (DNS ≥ 3 cm and height ≥ 1 m) and collected soil sampling to evaluate the potential effect of soil chemical composition. In addition, we correlate the effects of landscape structure on taxonomic, phylogenetic, and functional diversity, and the community weighted average for functional traits related to the provision of ecosystem services. Areas classified as closed vegetation and intermediate vegetation did not differ significantly regard species richness, phylogenetic and functional diversity, unlike open areas. Communities with vegetation in a more advanced state of regeneration (closed and intermediate) occurred in chemically richer soils (higher values of TOC = total organic carbon and N = total soil nitrogen). Regarding ecosystem services, there was no significant difference between the three levels of coverage, indicating that regard the analyzed fragments there was no loss of ecosystem services. We suggest here that landscapes susceptible to desertification, that still have remnants of native vegetation, have a high potential for regeneration and maintenance of ecosystem service provision.